2011
DOI: 10.1097/mcg.0b013e3182166a5a
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Assessment of Patient-reported Outcomes in Adults With Eosinophilic Esophagitis

Abstract: Our study demonstrated that EoE has substantial impact on several psychosocial domains that are not adequately addressed by focused assessment of physical complaints of dysphagia. The results support the importance of development of disease-specific instruments pertaining to quality of life in EoE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 0 publications
5
69
1
3
Order By: Relevance
“…No symptom is pathognomonic for EoE, and symptoms cannot be used in isolation to diagnose EoE because validated symptom metrics are still under development. 100,[286][287][288][289] Typical endoscopic features include pallor, furrows, rings, exudates, narrowing, and strictures, but endoscopic features in the absence of biopsy should not be used to diagnose EoE. 100,290 Subjects with suspected EoE should be treated with high-dose PPIs to rule out acid-induced esophageal infiltration of eosinophils.…”
Section: Section V: Adverse Reactions To Food Additivesmentioning
confidence: 99%
“…No symptom is pathognomonic for EoE, and symptoms cannot be used in isolation to diagnose EoE because validated symptom metrics are still under development. 100,[286][287][288][289] Typical endoscopic features include pallor, furrows, rings, exudates, narrowing, and strictures, but endoscopic features in the absence of biopsy should not be used to diagnose EoE. 100,290 Subjects with suspected EoE should be treated with high-dose PPIs to rule out acid-induced esophageal infiltration of eosinophils.…”
Section: Section V: Adverse Reactions To Food Additivesmentioning
confidence: 99%
“…The more general SF-36 questionnaire has only been used by one other research team for an EoE study [30]. Taft et al showed using qualitative interviews that patients with EoE have concerns about impact of eating, dysphagia episodes and available treatments among other things but Eur Arch Otorhinolaryngol also that they felt a relief upon receiving diagnosis [31]. The same authors have also developed a recent adult EoE quality of life questionnaire [32].…”
Section: Discussionmentioning
confidence: 97%
“…The aforementioned qualities of EGIDs, associated symptom burden, and limited treatment options can impact several psychosocial aspects within a patients’ health-related quality of life (HRQOL) 6, 7 . Patients with an EGID have reported an interference in social relationships and interactions, such as experiencing worry about eating in restaurants, scaring others, and hiding choking from others 6, 7 .…”
Section: Introductionmentioning
confidence: 99%